Pengaruh Viral Marketing dan Costumers Trust terhadap Buying Decision Melalui Media Promosi Akun Instagram @Kuliner_Lampung dalam Perspektif Bisnis Islam : (Studi pada Followers Akun Instagram @Kuliner_Lampung) - Eka Yulianti; Farid Fadhilah Prayogi; Wenny Rosilawati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Current developments in consumer behavior, most company business activities use the internet network. This is also done by companies when carrying out promotions. One of the activities carried out by the company is carrying out promotions using the internet network or better known as digital marketing. There are many developments in internet technology that are used in business marketing activities (e-marketing), one of which is currently developing is Viral Marketing. Viral marketing is carried out so that the message conveyed can be passed on by the recipient, resulting in multiple distributions. Viral marketing works like spreading a virus which aims to ensure that advertising messages communicated to the public can be disseminated many times over to other people. A consumer's trust in a company is really needed because businesses through viral marketing use the internet network, which means they don't meet each other face to face in transactions.